Functional role of autophagy in testicular and ovarian steroidogenesis - Afzal, Ali; Zhang, Yue; Afzal, Hanan; Saddozai, Umair Ali Khan; Zhang, Lei; Ji, Xin-Ying; Khawar, Muhammad Babar (Frontiers in Cell and Developmental Biology, 2024)
Autophagy is an evolutionarily conserved cellular recycling process that maintains cellular homeostasis. Despite extensive research in endocrine contexts, the role of autophagy in ovarian and testicular steroidogenesis remains elusive. The significant role of autophagy in testosterone production suggests potential treatments for conditions like oligospermia and azoospermia. Further, influence of autophagy in folliculogenesis, ovulation, and luteal development emphasizes its importance for improved fertility and reproductive health. Thus, investigating autophagy in gonadal cells is clinically significant. Understanding these processes could transform treatments for endocrine disorders, enhancing reproductive health and longevity. Herein, we provide the functional role of autophagy in testicular and ovarian steroidogenesis to date, highlighting its modulation in testicular steroidogenesis and its impact on hormone synthesis, follicle development, and fertility therapies.